MEDICAL WASTES MANAGEMENT A POLICY REVIEW - Ahmad Ganis (Program Studi Manajemen Lingkungan, 2013)
Abstract Since so many mishandling of medical waste in various places in Indonesia that has endangered our environment by the potential disease that easily can spread to our society , it is very important for all of us to address it on how to improve the medical waste management. There are area of improvement needed in our regulation, public policies disciplines and social awareness and especially the importance of proper handling of medical waste by the medical waste producers such as hospital, clinic and laboratories. This study is not intended to produce scientific theory but more focus on how to solve the problem of medical waste with the limit time and less costly manner or in the other words as a macro diagnosis of â€œthe main causes of the problemsâ€ of medical waste management in Indonesia. This study has made clear conclusion that Indonesia has to follow the basic principle and guidelines of International standards and recommends improvement of the coordination between Ministry of Health and Ministry of Environment, toward â€œone roof policyâ€, â€œstrong political will of top government to empower MOE and also Law No. 18, 2008 and Law No. 32, 2009 must be reviewed toward â€œPolluter pay the priceâ€ Policy. The government also must allocate sufficient fund to function as regulator and controlling body and increase social awareness for environmental health. Key note: Medical waste, public policy, environmental health